Simulation of microwave bistatic radar for breast cancer detection application - Samijayani, Oktarina Nur (2011)
The implementation of microwave active imaging technique for breast cancer detection is being developed recently and highly supported by the property of tumor which has high contrast in electrical properties compared to normal breast tissue. The tumor causes a significant scattering than normal tissue when exposed in microwave. Ultra wideband (UWB) microwave bistatic radar is simulated with a moving transmitter in the edge of breast utilizing the Doppler parameter for breast cancer detection. Doppler frequency is derived in terms both the changing of UWB pulse width and Pulse Repetition Frequency (PRF). The received signal is modelled and then processed using three Doppler Extraction Methods; Power Frequency Analysis, Correlation Method, and Doppler Frequency Separation. Doppler Frequency Separation is a better technique to extract the Doppler feature. Although the frequency changing caused by the Doppler Effect in this proposed system is small enough compared to its carrier frequency, the comparison result using correlation coefficient formula obtains the feasibility of this proposed radar to differentiate between a healthy and cancerous breast is about 0.2-0.5 of dissimilarity level.